The added value of the knowledge assets using a scale (VAIC) in a sample of the industrial sector companies - محمد, اياد طاهر; محمد, علياء جاسم (Journal of Economics and Administrative Sciences, 2017)
The sustainable competitive advantage for organizations is one of the requirements for value creation, which centered on the possession of scarce resources that achieve maximum flows to invest in intellectual capital, if what has been interest in them, measured and employed the way properly and style, so I figured the need for new technologies to enable organizations to measure the intellectual and physical assets and to assess its performance accordingly, so it sheds search light on the measurement of the added value of existing knowledge using the standard value-added factor is the intellectual (value added intellectual coefficient) (VAIC) and to develop a set of assumptions about the extent of the difference between the sample companies that have been picked up from the industrial sector companies trading of its shares in the Securities of the Iraqi market, which offers different products between pharmaceutical and clothes and food, engineering and texture, and to reach a number of conclusions which are summarized from the depreciation of human capital coefficient of Finance and the unit invested in by those companies with capital structural form of a remarkable increase compared to the size spending, The added value achieved through it.